Rh-Ni/CeO2-Al2O3 catalysts for methane dry reforming - Ocsachoque, Marco Antonio (2011)
A series of Ni and RhNi catalysts supported on Al2O3 modified by CeO2 (3 and 5 wt%, Ce) was studied for CO2 reforming of methane. Catalysts were characterized by hydrogen chemisorption, TPR, XRD, XPS, BET, TEM and dry reforming reaction tests. The influence of calcination temperature and Ce loading on activity and stability of mono and bimetallic samples was studied. The effect of Rh and Ce addition to Ni/Al2O3 catalyst improves the activity. Results show that the catalyst content 3%w/w Ce calcined at 650ºC, present higher reforming activity and stability than the unpromoted catalyst. The higher catalytic activity is attributed to the interaction between Rh and Ce phases, which has been verified by TPR experiments that improve the Rh dispersion and increase the catalyst active surface. The Rh addition on CeAl2O3 support increases the resistance to deactivation by carbon deposition.